Perencanaan Dan Model Pengembangan Sumber Daya Manusia Pendidikan Di Madrasah - Izzuddin, Moh; Cahyani, Dewi; Ali, Moh (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE ROLE OF HUMAN RESOURCE MANAGEMENT IN BUILDING A CULTURE OF INNOVATION IN EDUCATIONAL INSTITUTIONS Improving the quality of teaching staff in madrasah is crucial for enhancing the quality of education, both academically and religiously. The purpose of this article is to explain the importance of effective teaching staff planning, analyze appropriate development strategies, and provide a method that focuses on teacher well-being and morale. This study employed a qualitative descriptive method. Data collection utilized a literature review, analyzing various sources such as accredited journals, books, and educational policy documents. The results indicate that effective teaching staff development involves a combination of teacher well-being, morale, and work culture. Implementing a sustainable and planned strategy can enhance teacher professionalism, improve the quality of the teaching and learning process, and strengthen educational management in madrasas.